Effect of Nitrogen Sources and Weed Management Options on Weed Growth and Crop Yield of Transplant Aman Rice (Bangladesh Agronomy Journal, 2017)
A field study was conducted at the Agronomy research field of Bangladesh Agricultural University, Mymensingh, during the period of July to December, 2013 to evaluate the sources of nitrogen and weed management options on weed growth and rice yield. The experiment included four nitrogen sources (100% cowdung, 100% prilled urea, 100% urea super granule, 50% cowdung + 50% prilled urea) and four weed management options (weedy, application of herbicide at 3 DAT, application of herbicide at 3 DAT followed by hand weeding at 21 DAT and weed free). Sources of nitrogen and weed management options had significant effect on tiller number, biomass, SPAD value, panicle number, number of florets panicle-1, grain and straw yield, and weed biomass. The highest grain yield (5.40 t ha-1) was found in the treatment of 50% cowdung + 50% prilled urea with combination of season long weed free. Although 100% prilled urea had significantly similar grain yield to 50% cowdung + 50% prilled urea, however, across the weed management options, 100% urea super granule and 100% cowdung had 15 and 27% lower grain yield. Irrespective of the weed management options, 100% prilled urea had always higher weed biomass and 100% USG, 50% cowdung + 50% prilled urea, and 100% cowdung had 46, 35 and 19% lower weed biomass, respectively, compared with 100% prilled urea. In terms of rice yield and weed management, combined application of organic and inorganic source of nitrogen is better than only chemical or only organic source and pre-emergence herbicide followed by one hand weeding for transplanted aman rice.Bangladesh Agron. J. 2017, 20(1): 85-97